ANALYZING NATIONAL DEBT: IMPLICATIONS AND STRATEGIES IN FISCAL POLICY - Egamberdiev Oybek Romanberdievich (American Journals, 2022)
Public debt plays a crucial role in fiscal policy, enabling governments to finance essential expenditures and stimulate economic growth. However, its accumulation beyond sustainable levels poses challenges to economic stability. This article examines the implications of public debt on economic growth, discusses effective management strategies, and analyzes the impact of global events on debt dynamics. Insights highlight the importance of fiscal resilience, institutional reforms, and strategic policy responses in navigating the complexities of public debt for sustainable development.
Keywords: Public debt, fiscal policy, economic growth, debt management, fiscal resilience.